The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/fbp.0000000000000632
|View full text |Cite
|
Sign up to set email alerts
|

TrkB agonist 7,8-dihydroxyflavone reverses an induced prepulse inhibition deficit selectively in maternal immune activation offspring: implications for schizophrenia

Abstract: Reduced brain-derived neurotrophic factor (BDNF) signalling has been implicated in schizophrenia endophenotypes, including deficits in prepulse inhibition (PPI). Maternal immune activation (MIA) is a widely used neurodevelopmental animal model for schizophrenia but it is unclear if BDNF and its receptor, tropomyosin receptor kinase B (TrkB), are involved in PPI regulation in this model. Pregnant Long Evans rats were treated with the viral mimetic, polyinosinic–polycytidylic acid (poly I:C; 4 mg/kg i.v.), and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…In this study, there were no differences in PPI performance following either prenatal poly(I:C) or adolescent THC treatment. Although other groups have reported PPI deficits in rodents treated with prenatal poly(I:C) [ 11 , 23 ], these effects have not been universally demonstrated [ 24 , 25 ]. The origin of breeders [ 26 ] and the timing and dosing of poly(I:C) [ 19 ] have been found to affect PPI response.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there were no differences in PPI performance following either prenatal poly(I:C) or adolescent THC treatment. Although other groups have reported PPI deficits in rodents treated with prenatal poly(I:C) [ 11 , 23 ], these effects have not been universally demonstrated [ 24 , 25 ]. The origin of breeders [ 26 ] and the timing and dosing of poly(I:C) [ 19 ] have been found to affect PPI response.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of 7,8-DHF as a direct PDXP inhibitor was unexpected. Interestingly, numerous in vivo studies have reported the effectiveness of 7,8-DHF in brain disorder models, including rodent models of Alzheimer's disease (50)(51)(52)(53)(54)(55)(56)(57), depression (58)(59)(60)(61)(62)(63), schizophrenia (64)(65)(66)(67)(68), epilepsy (69,70) and autism (71)(72)(73)(74). Although PLP deficiency is thought to contribute to the respective human conditions (3,75,76), PLP-dependent processes have not yet been considered in the context of 7,8-DHF-induced effects.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments aimed at stimulation of the BDNF receptor, tropomyosin receptor-kinase B (TrkB), may prove clinically beneficial in counteracting the effects of METH, at least on PPI, and this may extend to psychosis and schizophrenia more generally. Indeed, recently, we showed that treatment with a TrkB receptor agonist could counteract PPI deficits in a maternal immune activation model of psychosis [ 73 ]. Moreover, in other psychosis and schizophrenia models, TrkB receptor activation has also shown promising results [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%